2017
DOI: 10.1186/s41606-017-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Practical considerations for effective oral appliance use in the treatment of obstructive sleep apnea: a clinical review

Abstract: Oral appliance (OA) therapy is a promising alternative to continuous positive airway pressure (CPAP) for patients with obstructive sleep apnea (OSA). By holding the mandible in a forward position, an OA keeps the airway open and prevents collapse. The recently revised practice parameters of the American Academy of Sleep Medicine extend the indications for OA therapy, recommending that "sleep physicians consider prescription of an OA for adult patients with OSA who are intolerant of CPAP therapy or prefer alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
2
0
1
Order By: Relevance
“…Протипоказаннями для лікування за допомогою цих пристроїв є стани ротової порожнини з менш ніж 10 зубами на дугу, оскільки цей стан призводить до нижчої ретенції. За наявності достатньої кількості зубів інші протипоказання включають дисфункцію скронево-нижньощелепного суглоба (СНЩС), серйозну рухливість зубів і захворювання пародонту [17].…”
Section: матеріали і методиunclassified
“…Протипоказаннями для лікування за допомогою цих пристроїв є стани ротової порожнини з менш ніж 10 зубами на дугу, оскільки цей стан призводить до нижчої ретенції. За наявності достатньої кількості зубів інші протипоказання включають дисфункцію скронево-нижньощелепного суглоба (СНЩС), серйозну рухливість зубів і захворювання пародонту [17].…”
Section: матеріали і методиunclassified
“…This approach of action is most likely involves a structural change to the pharynx enlarging the retroglossal airway via forward displacement of the tongue or lateral airway expansion. Several studies had been done to prove the efficiency of these appliances, in treatment both snoring and OSA [4]. According to Kushida et al [5], American Academy of Sleep Medicine suggested OA therapy as a first-line treatment in patients with mild to moderate OSA and for patients with more severe OSA who fail treatment attempts with CPAP therapy.…”
mentioning
confidence: 99%
“…This could include loss of control of the disease, unacceptable adverse effects requiring a stop to OAT, or important procedures to manage adverse effects such as orthodontic, temporo-mandibular joint, or restorative interventions. [9][10][11] Nonetheless, such studies would require robust selection protocols to increase effectiveness in predicting treatment response of OAT. 12,13 Newer OAT devices are designed with more than control of disease in mind.…”
mentioning
confidence: 99%